Thermal investigation into the Oldroyd-B hybrid nanofluid with the slip and Newtonian heating effect: Atangana–Baleanu fractional simulation - Ali, Qasim; Amir, Muhammad; Raza, Ali; Khan, Umair; Eldin, Sayed M.; Alotaibi, Abeer M.; Elattar, Samia; Abed, Ahmed M. (Frontiers in Materials, 2023)
The significance of thermal conductivity, convection, and heat transmission of hybrid nanofluid (HNF) based on different nanoparticles has rehabilitated an integral part of numerous industrial and natural processes. In this article, a fractionalized Oldroyd-B HNF along with the other significant impacts such as Newtonian heating, constant concentration, and wall slip condition on temperature close to an infinitely vertical plate has been examined, which further classifies the behavior of heat transmission and HNF flow. Aluminum Oxide (Al2O3), and Ferro ferric Oxide (Fe3O4) is considered nanoparticles, and water (H2O) and sodium alginate (C6H9NaO7) as the base fluids. In view of generalized memory effects, an innovative fractional model is developed based on the recently proposed Atangana-Baleanu time-fractional (AB) derivative through generalized Fourier and Fick's law. This Laplace transform technique is used to solve the fractional governing equations of dimensionless temperature, velocity, and concentration profiles. The physical effects of diverse parameters such as α,Pr,ϕ_1,ϕ_2,Gr,Gm are discussed and exhibited graphically by utilizing Mathcad software. Moreover, to validate our present results, some limiting models such as classical Maxwell and Newtonian fluid are recovered from AB fractional Oldroyd-B fluid model. Furthermore, compare the results between Oldroyd-B, Maxwell, and viscous fluid for both classical and fractional cases. Stehfest’s and Tzou’s numerical methods are also hired to secure the validity of our solutions. Moreover, it is visualized that for a small value of time, temperature and momentum profiles are decayed for larger values of α, and this effect is reversed at a large time. Furthermore, the energy and velocity profiles are larger for water-based HNF than the sodium alginate-based HNF.